Análisis de la usabilidad de YouTube/Chat GPT en el aprendizaje autónomo de estudiantes de 4to, 5to y 6to ciclo de la Carrera de Administración de Empresas de la Universidad Nacional de Loja - periodo septiembre 2023 - marzo 2024 - González Encalada, Estefanía Soledad (2024)
The following study research the Usability of YouTube/Chat GPT in the autonomous learning of 4th, 5th and 6th cycle of students in the Business Administration Career of the National University of Loja, during the September 2023 – March 2024 period, The study was done through a market research and to obtain the necessary information a survey was carried out, with which we obtained very interesting and peculiar results, so that both tools are positively valued by the students, in their process of autonomous and extracurricular learning. Subsequently, according to the result it was observed that 19% of the students mention that YouTube is very useful, because it helps them to solve study problems, while only 13,10% indicate that Chat has helped them in their students, however, it turns out that the majority indicate that the two are very useful to do their work, resulting in 57. Therefore, the two tools are important, since they indicate that they find them effective, as long as they use them together, we the two tools; YouTube and Chat GPT, with the purpose of solving study problems in an autonomous way. On the other hand, it can be highlighted that YouTube has a higher percentage of selection compared to Chat GPT, which is deduced that this tool is more popular, however Chat GPT has been created recently, therefore, its potential and how it would help in education is not yet know, as long as it is used appropriately. Finally, the challenge of the research is to know the use that students make of technological tools, how they can change the learning autonomy of each of the respondents and if they manage to learn only with the use of these tools or if they always need the guidance of a teacher in their academic and professional training.